Partisipasi Perawat dalam Penelitian Keperawatan dan Barier yang Mempengaruhinya - Pius A. L. Berek; Antonius Ngadiran; Maria Suryani; Christina Anugrahini (Universitas Muhammadiyah Manado, 2024)
Nurses' participation in nursing research is essential to support evidence-based practice. However, the level of nurses' involvement in research is still low. This study aims to identify the level of nurses' participation in nursing research, available resources, and barriers that influence it.. The study used a quantitative descriptive design with a sample of 332 nurses from various healthcare facilities on Timor Island. Data were collected using a structured questionnaire in a Google form and analyzed descriptively. The results showed that the highest involvement of nurses in research was as data collectors (49.1%) and research members (47.6%). In comparison, participation in proposal-making (32.8%), data analysis (34.6%), international publications (14.5%), and international conference presentations (15.4%) were still very low. Most nurses had access to training (76.5%) and supporting resources (75.9%). However, the main barriers included the perception that research was not relevant to nursing practice (85.8%), research was considered uninteresting (84.1%), and a sense of intimidation when conducting research (76.4%). Personal and institutional barriers cause low participation of nurses in research despite adequate resources. Strategies such as improving research training, developing a research culture in the workplace, and incentive policies are needed to increase nurse involvement in nursing research.